PENGARUH RESPONSIVENESS DAN QUALITY PRODUCT TERHADAP CUSTOMER SATISFACTION PADA RESTORAN SEA SKY LOVINA BEACH CLUB - Gede Dedy Prasetya; Putra, Komang Endrawan Sumadi (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
This study aims to examine the effect of responsiveness and product quality on customer satisfaction at Sea Sky Lovina Beach Club restaurant. This study is intended to offer a new perspective for restaurant managers to retain their customers satisfaction. The population of this study is the customers of Sea Sky Lovina Beach Club restaurant. The sampling technique used is simple random sampling. This study uses a questionnaire from 100 customers who dine at Sea Sky Lovina Beach Club restaurant. Multiple linear regression analysis was used to analyze the collected data with the assistance of SPSS software version 25. The results of the study indicate that responsiveness and product quality have a significant effect on customer satisfaction. Responsiveness has a positive and significant effect on customer satisfaction. Product quality has a positive and significant effect on customer satisfaction. The results of this study provide restaurant managers with an understanding of the importance of maintaining responsiveness and product quality to improve customer satisfaction at their restaurants.